Estimating Dynamic and Flow Characteristics of Electromagnetic Dispenser for The Kraz Truck Converted to Gas - V., Manoylo; Shch., Arhun; V., Migal; H., Hnatova; V., Korohodskyi; E., Zenkin; I., Shevchenko (International Journal of Integrated Engineering, 2023)
The problems of worldwide environmental degradation, global warming, scarcity of fossil fuels have caused the replacement of ICE vehicles with electric ones. For the countries with underdeveloped economy, it is important to find more affordable ways to solve this problem. One of them is to convert the cars with ICE into more environmentally friendly and economical ones, such as gas-powered cars. Yet, the conversion of diesel cars usually results in power loss. The work of the electromagnetic gas dispenser (EGD) of the engine power supply system significantly affects the efficiency of the gas engine. Therefore, the aim of the study was to determine the dynamic and flow characteristics of the EGD of the KrAZ truck (Ukraine) converted to gas, and to provide recommendations for improving the efficiency of its operation. The object of the research was the working processes of the EGD power supply system of 6ChGN13/14 engine, converted from diesel engine and equipped with a gas turbine supercharger. The paper presents the results of experimental studies on determining the effect of operating voltage on the dynamic characteristics of EGD. The dependences of dynamic and flow characteristics of the EGD on the change of the control signal frequency and the dependence of efficiency through the EGD flow nozzle on the control signal duration were obtained; the effect of the return spring stiffness on the dynamic and flow characteristics of the EGD were determined. The results of the work are designed to increase the efficiency of diesel trucks converted to gas.